Analisis Perbaikan Kualitas pada Produksi Printing Kain Cotton Menggunakan DMAIC dan Kaizen di PT. TFX - Wulandari, Ristanti Ayu; Hendrawan, Aloysius Tommy; Susanto, Doni (Fakultas Teknik Universitas Tulang Bawang, 2026)
The role of the textile industry is very important because this industry is involved in the supply of clothing. This research was conducted at Company TFX located in Central Java Province. There is a problem of a relatively high defect rate, hence improvements are needed. The method used is Six Sigma with a DMAIC approach (Define, Measure, Analyze, Improve, and Control) and Kaizen with a 5S approach to analyze quality management improvements at the company. The results of this study indicate that there are various types of defects, but the highest defect type is Folding Marks with a defect count of 39,211 yards and closed screen defects of 39,167 yards. The sigma value calculated is 3.24. Additionally, the analysis using Kaizen can be summarized as follows: organizing items that have been used, tidying up materials and tools used, cleaning tools and production areas and conducting a briefing for the employees. Keywords: Kaizen, Quality Control, Six Sigma